Simulating aero-engine performance and emissions characteristics running on green diesel - Altarazi, Yazan S. M.; Abu Talib, Abd. Rahim; Yu, Jianglong; Gires, Ezanee; Abdul Ghafir, Mohd Fahmi; Lucas, John; Yusaf, Talal (Taylor and Francis, 2022)
Green fuel is interconverted to another type of fuel. One of the alternative energy sources is green diesel. Despite its similar hydrocarbons molecular formula, it has better environmental properties and effects than petroleum diesel. This study aims to run a Kingtech K-180 turbojet engine using green diesel fuel (produced of waste cooking oil through a deoxygenating process) and its blend. The pure green diesel (GD100) and its blend (GD20 and GD5) parameters were calculated via GasTurb Details software. The engine performance and its emissions were predicted using GasTurb-13 software. All results presented show that green diesel gave lower specific fuel consumption and W_CO emission rate than diesel. However, green diesel and its blends lower EINOx emission fuel values than diesel due to its high heating value. The green diesel and its blend could be used as an alternative fuel in aviation engines.